2013
DOI: 10.1002/2013gc004931
|View full text |Cite
|
Sign up to set email alerts
|

Westerly jet‐East Asian summer monsoon connection during the Holocene

Abstract: [1] The causes of spatial and temporal changes in East Asian summer monsoon (EASM) precipitation on millennial to multimillennial time scales during the Holocene have not yet been resolved. Here, we examine the relationship between spatial variations in EASM precipitation and the westerly jet (WJ) path over East Asia during the Holocene using the provenance of eolian dust in Japan Sea sediments, which we interpret to reflect changes of the WJ path over East Asia and/or surface conditions of desert areas. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 63 publications
6
66
0
Order By: Relevance
“…3h, the WNP high shifts northward and matures in mid-June, a month ahead of that in the presentday simulation. This earlier break is consistent with a proxy record of Japan Sea sediments that shows an earlyHolocene environment drier than that in the present day (Nagashima et al 2013). …”
Section: Modulation Of Seasonalitysupporting
confidence: 88%
See 2 more Smart Citations
“…3h, the WNP high shifts northward and matures in mid-June, a month ahead of that in the presentday simulation. This earlier break is consistent with a proxy record of Japan Sea sediments that shows an earlyHolocene environment drier than that in the present day (Nagashima et al 2013). …”
Section: Modulation Of Seasonalitysupporting
confidence: 88%
“…As the precession-modulated Northern Hemisphere summer insolation decreased after the early Holocene, the "summer optimum" over East Asia (i.e., the timing of peak Holocene rainfall) shifted southwards from northern China in the early Holocene, to central China in the mid-Holocene, and to southern China in the late Holocene . Nagashima et al (2013) furthermore suggested that the path of the westerly jet over East Asia varied over the Holocene, apparently in concert with the spatial-temporal variation in East Asian summer precipitation intensity.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, the application of two single-grain techniques focusing on coarse-grained minerals revealed no apparent provenance shift on the CLP between glacial and interglacial periods (Che and Li, 2013;. However, the ESR signal intensity and crystallinity index (CI) of fine-grained quartz revealed that the provenance of fine dust on the CLP and in the Japan Sea varied at glacial-interglacial timescales (Nagashima et al, , 2013Sun et al, 2008). Different conclusions regarding dust provenance variations are likely due to the different tracers and/or grain-size fractions used in previous work.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the stable physical and chemical properties of quartz (Xiao et al, 1995), ESR signal intensity and CI, which reflect respectively the formation age and temperature of the host rocks (Murata and Norman, 1976;Toyoda and Naruse, 2002), have been measured intensively in order to trace the provenance of aeolian dust deposits on the CLP and in the Japan Sea (Nagashima et al, , 2011(Nagashima et al, , 2013Sun et al, 2007Sun et al, , 2008Sun et al, , 2013. Previous studies have confirmed that ESR and CI of quartz can effectively distinguish dust provenance.…”
Section: Introductionmentioning
confidence: 99%